2018
DOI: 10.1186/s12870-018-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs of switchgrass (Panicum virgatum L.) in multiple dehydration stresses

Abstract: BackgroundLong non-coding RNAs (lncRNAs) play important roles in plant growth and stress responses. Studies of lncRNAs in non-model plants are quite limited, especially those investigating multiple dehydration stresses. In this study, we identified novel lncRNAs and analyzed their functions in dehydration stress memory in switchgrass, an excellent biofuel feedstock and soil-conserving plant in the Gramineae family.ResultsWe analyzed genome-wide transcriptional profiles of leaves of 5-week-old switchgrass plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 84 publications
0
26
0
Order By: Relevance
“…We found that phosphoprotein phosphatase activity, protein metabolic process, and sequence-specific DNA binding were significantly and specially enriched in Q2, while single-organism metabolic process, photosynthesis, and oxidoreductase activity were significantly and specially enriched in Qinyou8. Additionally, lncRNAs have been recognized as powerful regulators of pathways in response to drought stress, including ribosome, photosynthesis [73], and plant hormone signal transduction [42,74]. The ribosome pathway was simultaneously significant in both genotypes, and the differential lncRNA target genes were up-regulated in this pathway.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%
“…We found that phosphoprotein phosphatase activity, protein metabolic process, and sequence-specific DNA binding were significantly and specially enriched in Q2, while single-organism metabolic process, photosynthesis, and oxidoreductase activity were significantly and specially enriched in Qinyou8. Additionally, lncRNAs have been recognized as powerful regulators of pathways in response to drought stress, including ribosome, photosynthesis [73], and plant hormone signal transduction [42,74]. The ribosome pathway was simultaneously significant in both genotypes, and the differential lncRNA target genes were up-regulated in this pathway.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%
“…chinensis), some TFs were cis-regulated by the response of lncRNAs to heat stress [117]. Under water stress and during recovery, 189 TFs corresponded to 163 differentially expressed lncRNAs in C. songorica, and there was a bZIP gene predicted to be the target gene of an lncRNA (MSTRG.17203.1) [72]. These studies indicated that there was a regulatory relationship between lncRNAs and TFs.…”
Section: Transcription Factors Functioned Under Drought Stress and Rementioning
confidence: 94%
“…With advances in next-generation sequencing technology, many investigations have shown that lncRNAs exert their regulatory effects on gene expression levels, including epigenetic regulation, transcriptional regulation, and post-transcriptional regulation in the form of RNA [19]. It is known that sequence-specific DNA binding transcription factor activity [42,70], response to stimulus [71], response to abiotic stimulus [70], biosynthetic process [70], structural constituent of ribosome [58], photosynthesis [72] and oxidoreductase activity [72], which are regulated by some lncRNAs, have been reported in response to abiotic stresses, and these GO terms were identified in this study. To determine the similarity and differences between the two genotypes, the significantly enriched GO terms were compared.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%
“…We found that phosphoprotein phosphatase activity, protein metabolic process, and sequence-specific DNA binding were significantly and specially enriched in Q2, while single-organism metabolic process, photosynthesis, and oxidoreductase activity were significantly and specially enriched in Qinyou8. Additionally, lncRNAs have been recognized as powerful regulators of pathways in response to drought stress, including ribosome, photosynthesis [73], and plant hormone signal transduction [42,74]. The ribosome pathway was simultaneously significant in both genotypes, and the differential lncRNA target genes were up-regulated in this pathway.…”
Section: Differentially Expressed Lncrnas Specifically Enriched In Gomentioning
confidence: 99%